Subjective Well-being in Children: Measurement Tools and Age Dynamics - Archakova T.O (Moscow State University of Psychology and Education, 2018)
This review article deals with the methods for measurement of subjective well-being in children and adolescents. The first part of the review presents an outlook of several psychometric instruments that demonstrate various approaches to measuring subjective well-being: multidimensional and one-dimensional multiple-item scales as well as single item scales. The examples of techniques for establishing validity of developing instruments are provided. The experience of adaptation of psychometric instruments for measuring well-being to use them in younger samples is discussed. The article also highlights the discrepancies between parents' and children's own evaluations of children's well-being that are documented with the use of several instruments. The second part of the review deals with the issues of subjective well-being dynamics that should be captured by psychometric instruments. The hypotheses of stability of subjective well-being levels (the notions of "homeostatically protected mood" and "well-being set point") are discussed and contrasted to the results of empirical research of changes in normative levels of subjective well-being from preschool age to adolescence.